Kedudukan Perjanjian Pra-Nikah dalam Hukum Keluarga Islam dan Implementasinya di Pengadilan Agama - Andini, Dwi (Maliki Interdisciplinary Journal, 2026)
Generally, marriage is a connection, both physical and spiritual, between a man and a woman as husband and wife, aimed at creating a joyful and lasting family based on religious values. Different cultures and religions have their own rules about marriage. Under Islamic law and civil law, a prenuptial agreement is a contract made between the future husband and wife before marriage to manage specific aspects of their family life, especially regarding property. In Indonesian Islamic family law, prenuptial agreements are accepted as long as they do not contradict Islamic principles and the laws in force.